Enzymatic hydrolysis lignin PBAT composite material, degradable film and preparation method of degradable film

Through the composite material technology of enzymatic lignin and PBAT, the problems of poor mechanical properties and low resource utilization are solved, and efficient degradation and low-cost preparation of degradable films are achieved, which are suitable for plastic wrap and plastic film fields.

CN119144126APending Publication Date: 2024-12-17CATHAY BIOTECH INC +1

Patent Information

Application Number
CN202310713168.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing biodegradable plastic PBAT has poor mechanical properties and high cost, and the lignin resources in crop straw have not been fully utilized, resulting in waste of resources and environmental pollution.

Method used

The enzymatic lignin and PBAT composite material is used to prepare enzymatic lignin suitable for plastic wrap and mulch film by biorefining and modification of enzymatic lignin, combined with the double-screw extruder granulation and film blowing technology. PBAT composites and degradable membranes.

Benefits of technology

The complete degradation of enzymatic lignin PBAT composite material has been achieved, which improves the mechanical properties of the material, reduces raw material costs, increases the utilization rate of crop straw, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an enzymatic hydrolysis lignin PBAT composite material, a degradable film and a preparation method of the degradable film. The enzymatic hydrolysis lignin PBAT composite material comprises 8-45 parts by weight of enzymatic hydrolysis lignin, 55-92 parts by weight of PBAT and 1-10 parts by weight of a plasticizer. Therefore, the enzymatic hydrolysis lignin PBAT composite material meets the complete degradation requirement and is especially suitable for the field of preservative films and mulching films, the enzymatic hydrolysis lignin is wide in source and low in cost as a raw material, the national crop straw utilization rate can be increased, and environmental pollution can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of degradable plastics, and in particular to an enzymatically hydrolyzed lignin PBAT composite material, a degradable film and a preparation method thereof. Background Art

[0002] Plastic products have been applied to all aspects of life, making the quality of human life reach an unprecedented level, and greatly promoting the progress of human civilization. However, most of the existing plastic products are non-degradable and difficult to recycle, and their waste has seriously threatened the living environment of human beings. Therefore, in recent years, the research and development of new degradable plastics has become a hot topic in the field of current polymer materials. At present, the main degradable plastics are polybutylene terephthalate-adipate (PBAT), polylactic acid (PLA), polyglycolic acid (PGA), polybutylene succinate (PBS), etc. Among them, PBAT is polymerized with terephthalic acid, adipic acid and butanediol as raw materials, and has the performance of PBA (polybutylene adipate) and PBT (polybutylene terephthalate), and has a wide range of applications. However, PBAT has problems such as poor mechanical properties and high price, which limit its application to a certain extent. Therefore, it is necessary to carry out relevant modifications on PBAT to achieve the effect of reducing costs and improving comprehensive performance.

[0003] There are many kinds of crops in my country, mainly wheat, rice, corn, beans, potatoes, cotton, sugarcane and other grain crops. Straw is the remaining part after the seeds of crops are harvested, and it is a valuable biomass resource.

[0004] In order to make full use of crop straw, many domestic research institutions and enterprises are currently engaged in research and development of crop resource utilization, using crop straw to prepare bio-based raw materials. However, researchers often only focus on the cellulose in the straw, and do not develop the residue left after the straw is used to prepare bio-based raw materials. The residue is directly used as waste and low-quality solid fuel. However, lignin, another major component of straw, is basically present in this residue, which is not only not conducive to the comprehensive application of biorefining, but also causes great waste of resources and pollution to the environment. Summary of the invention

[0005] The present invention aims to solve one of the technical problems existing in the prior art. To this end, the present invention proposes an enzymatic lignin PBAT composite material, a degradable film and a preparation method thereof.

[0006] In one aspect of the present invention, the present invention provides an enzymatically hydrolyzed lignin PBAT composite material. According to an embodiment of the present invention, the enzymatically hydrolyzed lignin PBAT composite material comprises: 8 to 45 parts by weight of enzymatically hydrolyzed lignin, 55 to 92 parts by weight of PBAT, and 1 to 10 parts by weight of a plasticizer.

[0007] In the second aspect of the present invention, the present invention proposes a method for preparing the above-mentioned enzymatic lignin PBAT composite material. According to an embodiment of the present invention, the method comprises: (1) mixing the dried enzymatic lignin with PBAT and a plasticizer to obtain a premix; (3) extruding the premix through a twin-screw extruder to granulate, and then cooling and granulating to obtain the enzymatic lignin PBAT composite material.

[0008] In the third aspect of the present invention, the present invention provides an enzymatically hydrolyzed lignin PBAT degradable film. According to an embodiment of the present invention, the enzymatically hydrolyzed lignin PBAT degradable film is prepared by using the above enzymatically hydrolyzed lignin PBAT composite material.

[0009] In a fourth aspect of the present invention, the present invention proposes a method for preparing the above-mentioned enzymatic lignin PBAT degradable film. According to an embodiment of the present invention, the method comprises putting the enzymatic lignin PBAT composite material into a film blowing machine, and blowing the film to obtain the enzymatic lignin PBAT degradable film.

[0010] The present invention has the following beneficial effects:

[0011] (1) Enzymatic lignin PBAT composite materials meet the requirements of complete degradation and are suitable for the fields of cling film and mulch film;

[0012] (2) Enzymatic lignin is widely available and has low cost as a raw material. It can increase the utilization rate of crop straw in the country and reduce environmental pollution.

[0013] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0014] The present invention is further described below in conjunction with preferred embodiments and comparative examples. It should be noted that the described embodiments are only representative embodiments and cannot represent all embodiments. The content described below is illustrative rather than restrictive and should not be used to limit the scope of protection of the present invention.

[0015] In one aspect of the present invention, the present invention provides an enzymatic lignin PBAT composite material. According to an embodiment of the present invention, the enzymatic lignin PBAT composite material comprises: 8 to 45 parts by weight of enzymatic lignin, 55 to 92 parts by weight of PBAT and 1 to 10 parts by weight of plasticizer, preferably 10 to 40 parts by weight of enzymatic lignin, 60 to 85 parts by weight of PBAT, and 3 to 7 parts by weight of plasticizer.

[0016] According to a specific embodiment of the present invention, enzymatic lignin comes from a biorefining process, such as a process of preparing ethanol by enzymatic hydrolysis of corn stalks by microorganisms. Compared with the preparation process of sulfate lignin and alkali lignin, enzymatic lignin is not treated with high temperature and high pressure, and is obtained by organic solvent extraction. Therefore, a large number of active groups, especially phenolic hydroxyl groups, can be retained. At the same time, the chemical structure of enzymatic lignin is mainly aromatic rings, which has a promoting effect on improving the mechanical properties of the material. Therefore, by introducing enzymatic lignin into the biodegradable material PBAT, an enzymatic lignin PBAT composite material is obtained. The enzymatic lignin PBAT composite material is suitable for the field of cling film and mulch film, meets the requirements of complete degradation, and the enzymatic lignin is widely available. As a raw material, the cost is low, which can improve the utilization rate of crop straw in the country and reduce environmental pollution.

[0017] According to a specific embodiment of the present invention, the weight average molecular weight of the enzymatic lignin is 4000-6000, preferably 4500-5800, such as 4400, 4800, 5200, 5600, etc. The inventors found that when the molecular weight is too large, the content of active groups in the enzymatic lignin is relatively small, and there is a volume effect, which is not conducive to its reaction with the PBAT molecular chain; when the molecular weight is too small, the aromatic ring content of the enzymatic lignin is relatively small, and it is easy to agglomerate, which cannot well improve the mechanical properties of the composite material.

[0018] According to a specific embodiment of the present invention, the particle size of the enzymatic lignin is 1-10 μm, preferably 4-8 μm, such as 2 μm, 3 μm, 5 μm, 6 μm, 7 μm, 9 μm, etc. The inventors found that when the particle size is too large, the enzymatic lignin will destroy the interaction between the molecular chains of the resin matrix; and when the particle size is too small, the enzymatic lignin will undergo serious agglomeration, resulting in uneven dispersion in the matrix.

[0019] According to a specific embodiment of the present invention, the methoxy content of the enzymatically hydrolyzed lignin is 11-13 wt%, for example, 11.5 wt%, 12 wt%, 12.2 wt%, 12.5 wt%, 12.8 wt%, and the like.

[0020] According to a specific embodiment of the present invention, the phenolic hydroxyl content of the enzymatic lignin is 3-5wt%, preferably 4-5wt%. The inventors found that due to the small volume and high activity of phenolic hydroxyl groups, a high phenolic hydroxyl content can significantly improve the reaction activity of the enzymatic lignin, but too high a phenolic hydroxyl content can also cause the enzymatic lignin to have poor dispersion.

[0021] According to a preferred embodiment of the present invention, the enzymatic lignin PBAT composite material also includes: 0.2 to 1 parts by weight of a heat stabilizer, 0.5 to 1.5 parts by weight of a lubricant, and 0.1 to 1 parts by weight of an antioxidant, preferably 0.3 to 0.6 parts by weight of a heat stabilizer, 0.8 to 1.2 parts by weight of a lubricant, and 0.2 to 0.6 parts by weight of an antioxidant.

[0022] According to a specific embodiment of the present invention, the above-mentioned PBAT is polybutylene terephthalate-adipate known in the art, which is a terpolymer of terephthalic acid, adipic acid and 1,4-butanediol. Preferably, the PBAT is a fully bio-based PBAT, which is obtained according to the method of the authorized patent CN104031246A. Therefore, the use of fully bio-based PBAT causes less pollution to the environment, can reduce carbon dioxide emissions, reduce the generation of greenhouse effects, and adapt to the development trend of carbon neutrality.

[0023] According to a specific embodiment of the present invention, the enzymatic lignin is a modified enzymatic lignin. Those skilled in the art can select the type of modified enzymatic lignin as needed, such as at least one of sulfonated enzymatic lignin, aminated enzymatic lignin, alkylated enzymatic lignin and etherified enzymatic lignin. Thus, the modified enzymatic lignin can act as a dispersant and compatibilizer, which can reduce the use of plastic additives, effectively reduce the production cost of PBAT products, and make its application scenarios more conducive to promotion.

[0024] According to a specific embodiment of the present invention, the enzymatically hydrolyzed lignin PBAT composite material further includes 0.05 to 2 parts by weight of a chain extender.

[0025] It should be noted that the types of the above-mentioned plasticizers are not particularly limited, and those skilled in the art can select as needed, for example, at least one of deionized water, glycerol, ethylene glycol, polyethylene glycol, triacetin, dibutyl sebacate, acetyl tri-n-butyl citrate, triethyl citrate and tributyl citrate; deionized water, glycerol and ethylene glycol are preferred, as they are abundant in source and inexpensive, and can reduce costs compared to most ester plasticizers.

[0026] It should be noted that the types of the above stabilizers are not particularly limited, and those skilled in the art can select as needed, for example, at least one of phosphoric acid, trimethyl phosphate, triphenyl phosphate, trimethyl phosphite and polyphosphoric acid.

[0027] It should be noted that the types of the above lubricants are not particularly limited, and those skilled in the art can select according to needs, such as at least one of calcium stearate, zinc stearate, and oleamide lubricants.

[0028] It should be noted that the types of the above antioxidants are not particularly limited, and those skilled in the art can select as needed, for example, at least one of the commercially available antioxidants 618, 1010, 1076, and 1178.

[0029] It should be noted that the type of the above chain extender is not particularly limited, and those skilled in the art can select as needed, for example, at least one of hydroquinone dihydroxyethyl ether, resorcinol dihydroxyethyl ether, bisphenol A, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, and ethylene glycol.

[0030] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned enzymatic lignin PBAT composite material. According to an embodiment of the present invention, the method comprises:

[0031] S100: Mix the dried enzymatic lignin with PBAT and plasticizer

[0032] In this step, the enzymatically hydrolyzed lignin and PBAT are vacuum dried to obtain dried enzymatically hydrolyzed lignin and PBAT. Specifically, the drying temperature is 25-40°C, the time is 1h-3h, and the vacuum degree is 0-5000Pa (absolute pressure); preferably, the drying temperature is 29-31°C, the time is 2-2.5h, and the vacuum degree is 500-1000Pa (absolute pressure). It should be noted that the vacuum drying device is not particularly limited, as long as the vacuum drying function is achieved, and it will not be repeated here.

[0033] According to a specific embodiment of the present invention, the enzymatically hydrolyzed lignin comes from a biorefining process and is obtained by an organic solvent extraction method.

[0034] According to a specific embodiment of the present invention, the weight average molecular weight of the enzymatic lignin is 4000-6000, preferably 4500-5800, such as 4400, 4800, 5200, 5600, etc.; the particle size of the enzymatic lignin is 1-10 μm, preferably 4-8 μm, such as 2 μm, 3 μm, 5 μm, 6 μm, 7 μm, 9 μm, etc.; the methoxy content of the enzymatic lignin is 11-13 wt%, preferably 12-13 wt%, such as 12.2 wt%, 12.5 wt%, 12.8 wt%, etc. The phenolic hydroxyl content of the enzymatic lignin is 3-5 wt%, preferably 4-5 wt%.

[0035] According to a specific embodiment of the present invention, the above-mentioned PBAT is polybutylene terephthalate-adipate known in the art, which is a terpolymer of terephthalic acid, adipic acid and 1,4-butanediol. Preferably, PBAT is a fully bio-based PBAT, and the fully bio-based PBAT is obtained according to the method of the authorized patent CN104031246A. Therefore, the use of fully bio-based PBAT causes less pollution to the environment, can reduce carbon dioxide emissions, reduce the generation of greenhouse effects, and adapt to the development trend of carbon neutrality.

[0036] According to a specific embodiment of the present invention, the enzymatic lignin is modified in advance, and the modification includes at least one of sulfonation, amination, alkylation and etherification. As a result, the enzymatic lignin can act as a dispersant and compatibilizer, which can reduce the use of plastic additives, effectively reduce the production cost of PBAT products, and make its application scenarios more conducive to promotion. The modified enzymatic lignin has better dispersibility, which further improves the mechanical properties of the composite material. It should be noted that the modification method is a conventional operation in the art and will not be repeated here.

[0037] In this step, the dried enzymatic lignin is mixed with PBAT and plasticizer to obtain a premix. Specifically, the mixing temperature is 95-105°C, the rotation speed is 800-1000r / min, and the mixing time is 10-20min. It should be noted that the mixing device is not particularly limited, such as a high-speed mixer, as long as the mixing function is achieved, which will not be repeated here.

[0038] According to a specific embodiment of the present invention, the premix includes 8 to 45 parts by weight of enzymatic lignin, 55 to 92 parts by weight of PBAT and 1 to 10 parts by weight of plasticizer, preferably 10 to 40 parts by weight of enzymatic lignin, 60 to 85 parts by weight of PBAT, and 3 to 7 parts by weight of plasticizer. The inventors found that within a certain ratio range of enzymatic lignin and PBAT, as the content of enzymatic lignin increases, the mechanical properties of the composite material gradually improve, but when the content of enzymatic lignin is too large, the mechanical properties of the composite material will drop sharply.

[0039] According to a specific embodiment of the present invention, the premix further comprises 0.2-1 parts by weight of a heat stabilizer, 0.5-1.5 parts by weight of a lubricant, and 0.1-1 parts by weight of an antioxidant, preferably 0.3-0.6 parts by weight of a heat stabilizer, 0.8-1.2 parts by weight of a lubricant, and 0.2-0.6 parts by weight of an antioxidant.

[0040] According to a specific embodiment of the present invention, the premix further comprises 0.05 to 2 parts by weight of a chain extender.

[0041] It should be noted that the types of the above-mentioned plasticizers are not particularly limited, and those skilled in the art can select as needed, for example, at least one of deionized water, glycerol, ethylene glycol, polyethylene glycol, triacetin, dibutyl sebacate, acetyl tri-n-butyl citrate, triethyl citrate and tributyl citrate; deionized water, glycerol and ethylene glycol are preferred, as they are abundant in source and inexpensive, and can reduce costs compared to most ester plasticizers.

[0042] It should be noted that the types of the above stabilizers are not particularly limited, and those skilled in the art can select as needed, for example, at least one of phosphoric acid, trimethyl phosphate, triphenyl phosphate, trimethyl phosphite and polyphosphoric acid.

[0043] It should be noted that the types of the above lubricants are not particularly limited, and those skilled in the art can select according to needs, such as at least one of calcium stearate, zinc stearate, and oleamide lubricants.

[0044] It should be noted that the types of the above antioxidants are not particularly limited, and those skilled in the art can select as needed, for example, at least one of the commercially available antioxidants 618, 1010, 1076, and 1178.

[0045] It should be noted that the type of the above chain extender is not particularly limited, and those skilled in the art can select as needed, for example, at least one of hydroquinone dihydroxyethyl ether, resorcinol dihydroxyethyl ether, bisphenol A, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, and ethylene glycol.

[0046] S200: The premix is ​​extruded into pellets through a twin-screw extruder, then cooled and pelletized

[0047] In this step, the premix is ​​extruded and granulated through a twin-screw extruder, and then cooled and pelletized to obtain an enzymatically hydrolyzed lignin PBAT composite material. Specifically, the extrusion temperature of the twin-screw extruder is 120-180°C, preferably 130-150°C.

[0048] It should be noted that the advantages described above for the enzymatically hydrolyzed lignin PBAT composite material are also applicable to the preparation method of the enzymatically hydrolyzed lignin PBAT composite material, and will not be repeated here.

[0049] In the third aspect of the present invention, the present invention provides an enzymatically hydrolyzed lignin PBAT degradable film, characterized in that the enzymatically hydrolyzed lignin PBAT degradable film is prepared by using the above-mentioned enzymatically hydrolyzed lignin PBAT composite material.

[0050] It should be noted that the advantages described above for the enzymatically hydrolyzed lignin PBAT composite material and its preparation method are also applicable to the enzymatically hydrolyzed lignin PBAT degradable film, and will not be repeated here.

[0051] In a fourth aspect of the present invention, the present invention proposes a method for preparing the above-mentioned enzymatic lignin PBAT degradable film. According to an embodiment of the present invention, the method comprises: putting the enzymatic lignin PBAT composite material into a film blowing machine, and blowing the film to obtain the enzymatic lignin PBAT degradable film. Specifically, the film blowing temperature of the film blowing machine is 120 to 190°C.

[0052] It should be noted that the advantages described above for the enzymatically hydrolyzed lignin PBAT degradable film are also applicable to the preparation method of the enzymatically hydrolyzed lignin PBAT degradable film, and will not be repeated here.

[0053] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0054] Bio-based terephthalic acid and enzymatic lignin were purchased from Cathay (Jinxiang) Biomaterials Co., Ltd.

[0055] In the present invention, the modification of enzymatic lignin is all prior art. For the same type of modification, different modification methods have little effect on it. The following sulfonation, amination, alkylation and etherification are all common modification methods in this field. For example, refer to "Chemical Modification Methods of Lignin and Their Application in Surfactants" published by Yang Ting and Che Guoyong in the second issue of "Sichuan Chemical Industry" in 2023, Volume 26, pages 16-21.

[0056] Preparation Example

[0057] Weigh 40.3g of bio-based terephthalic acid, 20.3g of adipic acid, 52.3g of 1,4-butanediol, 0.3g of titanium dioxide and silicon dioxide composite (titanium silicon molar ratio is 7:3) and 0.05g of magnesium acetate, mix them, heat to 130℃ and stir under nitrogen protection, and heat to 220℃ by programmed temperature rise (heating rate is 10℃ / min) after beating for 10min, and keep the temperature for 120min until the output of esterification water reaches 99wt% of the theoretical value. After the esterification reaction is completed, evacuate to an absolute pressure of less than 50Pa, react for 15min, remove the monomers and by-products that did not participate in the reaction in the system, continue to evacuate to an absolute pressure of less than 50Pa, set the reaction temperature to 235℃, and keep stirring quickly. React at a constant temperature for 150min under vacuum (the product viscosity increases and climbs the pole) to obtain bio-based PBAT.

[0058] Example 1

[0059] (1) vacuum drying unmodified enzymatically hydrolyzed lignin and bio-based PBAT at a temperature of 30° C. for 2 h and a vacuum degree of 1000 Pa (absolute pressure), wherein the unmodified enzymatically hydrolyzed lignin has a weight average molecular weight of 4520, a particle size of 6 μm, a methoxy content of 12.3 wt %, and a phenolic hydroxyl content of 4.2 wt %;

[0060] (2) Add 92 parts of dried bio-based PBAT, 8 parts of unmodified enzymatic lignin, 0.6 parts of antioxidant 1010, 2 parts of glycerol, 0.7 parts of triphenyl phosphate and 0.5 parts of zinc stearate into a high-speed mixer, respectively, and stir at 100° C. for 15 minutes at a speed of 900 r / min to obtain an enzymatic lignin PBAT premix;

[0061] (3) using a twin-screw extruder to extrude and granulate the enzymatically hydrolyzed lignin PBAT premix, controlling the extrusion temperature to about 130° C., to obtain enzymatically hydrolyzed lignin PBAT composite plastic particles;

[0062] (4) The enzymatically hydrolyzed lignin PBAT composite plastic particles were dried in a vacuum oven at 50°C for 12 h and then put into a film blowing machine. The film blowing temperature was controlled at about 130°C to prepare an enzymatically hydrolyzed lignin modified PBAT degradable film material.

[0063] Example 2

[0064] In step (2), the dried bio-based PBAT is 80 parts, the unmodified enzymatic lignin is 20 parts, and the rest is the same as in Example 1.

[0065] Example 3

[0066] In step (2), the dried bio-based PBAT is 70 parts, the unmodified enzymatic lignin is 30 parts, and the rest is the same as in Example 1.

[0067] Example 4

[0068] In step (2), the dried bio-based PBAT is 60 parts, the unmodified enzymatic lignin is 40 parts, and the rest is the same as in Example 1.

[0069] Example 5

[0070] In step (2), 1.0 part of 1,4-butanediol was also added to the high mixer, and the rest was the same as in Example 1.

[0071] Example 6

[0072] The enzymatically hydrolyzed lignin is subjected to sulfonation treatment to obtain sulfonated enzymatically hydrolyzed lignin, which is then applied to subsequent steps, with the rest being the same as in Example 1.

[0073] Example 7

[0074] (1) performing an amination treatment on the enzymatically hydrolyzed lignin to obtain an amination-enzymatically hydrolyzed lignin, wherein the enzymatically hydrolyzed lignin has a weight average molecular weight of 4520, a particle size of 6 μm, a methoxy content of 12.3 wt %, and a phenolic hydroxyl content of 4.2 wt %;

[0075] (2) vacuum drying the aminated enzymatic lignin and bio-based PBAT at a temperature of 30° C. for 2 h and a vacuum degree of 1000 Pa (absolute pressure);

[0076] (3) Calculated by weight, 80 parts of dried bio-based PBAT, 20 parts of aminated enzymatic lignin, 0.5 parts of antioxidant 1178, 3 parts of ethylene glycol, 0.6 parts of trimethyl phosphate, and 0.5 parts of calcium stearate were added to a high-speed mixer, and stirred at 100° C. for 15 minutes at a speed of 900 r / min to obtain an aminated enzymatic lignin PBAT premix;

[0077] (4) using a twin-screw extruder to extrude and granulate the aminated enzymatically hydrolyzed lignin PBAT premix, controlling the extrusion temperature to about 140° C., to prepare aminated enzymatically hydrolyzed lignin PBAT composite plastic particles;

[0078] (5) The aminated enzymatically hydrolyzed lignin PBAT composite plastic particles were dried in a vacuum oven at 50°C for 12 h and then put into a film blowing machine. The film blowing temperature was controlled at about 140°C to prepare an aminated enzymatically hydrolyzed lignin modified PBAT degradable film material.

[0079] Example 8

[0080] (1) alkylating the enzymatically hydrolyzed lignin to obtain alkylated enzymatically hydrolyzed lignin, wherein the enzymatically hydrolyzed lignin has a weight average molecular weight of 4520, a particle size of 6 μm, a methoxy content of 12.3 wt %, and a phenolic hydroxyl content of 4.2 wt %;

[0081] (2) vacuum drying the alkylated enzymatic lignin and bio-based PBAT at a temperature of 30° C. for 2 h and a vacuum degree of 1000 Pa (absolute pressure);

[0082] (3) Calculated by weight, 70 parts of dried bio-based PBAT, 30 parts of alkylated enzymatic lignin, 0.5 parts of antioxidant 618, 3 parts of triacetin, 0.6 parts of triphenyl phosphate, and 0.5 parts of calcium stearate were added to a high-speed mixer, and stirred at 100° C. for 15 minutes at a speed of 900 r / min to obtain an alkylated enzymatic lignin PBAT premix;

[0083] (4) Extruding the alkylated enzymatically hydrolyzed lignin PBAT premix into granules using a twin-screw extruder, controlling the extrusion temperature to about 140° C., to prepare alkylated enzymatically hydrolyzed lignin PBAT composite plastic particles;

[0084] (5) The alkylated enzymatically hydrolyzed lignin PBAT composite plastic particles were dried in a vacuum oven at 50°C for 12 h and then put into a film blowing machine. The film blowing temperature was controlled at about 140°C to prepare an alkylated enzymatically hydrolyzed lignin modified PBAT degradable film material.

[0085] Example 9

[0086] (1) etherifying the enzymatically hydrolyzed lignin to obtain etherified enzymatically hydrolyzed lignin, wherein the enzymatically hydrolyzed lignin has a weight average molecular weight of 4520, a particle size of 6 μm, a methoxy content of 12.3 wt %, and a phenolic hydroxyl content of 4.2 wt %;

[0087] (2) vacuum drying the etherified enzymatically hydrolyzed lignin and bio-based PBAT at a temperature of 30° C. for 2 h and a vacuum degree of 1000 Pa (absolute pressure);

[0088] (3) Add 60 parts of dried bio-based PBAT, 40 parts of etherified enzymatic lignin, 0.3 parts of antioxidant 1178, 7 parts of polyethylene glycol, 0.4 parts of trimethyl phosphite, and 1 part of calcium stearate to a high-speed mixer, respectively, and stir at 100° C. for 15 minutes at a speed of 900 r / min to obtain an etherified enzymatic lignin PBAT premix;

[0089] (4) using a twin-screw extruder to extrude and granulate the etherified enzymatically hydrolyzed lignin PBAT premix, controlling the extrusion temperature to about 160° C., to prepare etherified enzymatically hydrolyzed lignin PBAT composite plastic particles;

[0090] (5) The etherified enzymatically hydrolyzed lignin PBAT composite plastic particles were dried in a vacuum oven at 50°C for 12 h and then put into a film blowing machine. The film blowing temperature was controlled at about 160°C to prepare an etherified enzymatically hydrolyzed lignin modified PBAT biodegradable film material.

[0091] Comparative Example 1

[0092] Unmodified bio-based PBAT was used as comparative example 1, and the rest was the same as in example 1.

[0093] Comparative Example 2

[0094] The addition amount of enzymatic lignin was 5 parts, and the others were the same as in Example 1.

[0095] Comparative Example 3

[0096] The addition amount of enzymatic lignin was 55 parts, and the others were the same as in Example 1.

[0097] Comparative Example 4

[0098] The addition amount of sulfonated enzymatically hydrolyzed lignin is 5 parts, and the others are the same as in Example 6.

[0099] Comparative Example 5

[0100] The addition amount of sulfonated enzymatically hydrolyzed lignin was 55 parts, and the rest was the same as in Example 6.

[0101] The plastic particles prepared in each embodiment and comparative example were made into test samples that meet the GBT1040-2006 standard, and the tensile strength, elongation at break and other mechanical properties of the samples were tested using a WD-Ⅱ10 universal testing machine, wherein the tensile rate was 20 mm / min, and the biocomposting degradation experiment was carried out on the above samples in accordance with the national standard GB / T16716.7-2012. The relevant results are shown in Table 1.

[0102] Table 1 Test results of each sample

[0103] sample Tensile strength / MPa Elongation at break / % 6-month composting degradation rate / % Example 1 28.9 590 99 Example 2 31.1 544 98 Example 3 34.4 497 97 Example 4 36.8 435 97 Example 5 29.4 582 99 Example 6 32.0 601 99 Example 7 34.9 563 98 Example 8 38.8 518 97 Example 9 41.6 464 97 Comparative Example 1 23.5 677 99 Comparative Example 2 25.8 629 99 Comparative Example 3 33.7 355 97 Comparative Example 4 27.9 620 99 Comparative Example 5 37.0 392 97

[0104] From the test results in Table 1, it can be seen that the PBAT composite plastic sample modified by enzymatic lignin extracted from the enzymatic residue of crops can be completely degraded, and is particularly suitable for the fields of cling film and mulch film. Moreover, the enzymatic lignin itself can act as a compatibilizer and chain extender, and no additional additives are required, saving production costs. The above comparison can show the advantages of the present invention.

[0105] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. An enzymatically hydrolyzed lignin PBAT composite material, It is characterized in that The enzymatically hydrolyzed lignin PBAT composite material comprises: 8 to 45 parts by weight of enzymatically hydrolyzed lignin, 55 to 92 parts by weight of PBAT, and 1 to 10 parts by weight of plasticizer, preferably 10 to 40 parts by weight of enzymatically hydrolyzed lignin, 60 to 85 parts by weight of PBAT and 3 to 7 parts by weight of plasticizer.

2. The enzymatically hydrolyzed lignin PBAT composite material according to claim 1, It is characterized in that The weight average molecular weight of the enzymatically hydrolyzed lignin is 4000 to 6000; Optionally, the particle size of the enzymatically hydrolyzed lignin is 1 to 10 μm; Optionally, the phenolic hydroxyl content of the enzymatically hydrolyzed lignin is 3 to 5 wt%; Optionally, the methoxy content of the enzymatically hydrolyzed lignin is 11 to 13 wt%.

3. The enzymatically hydrolyzed lignin PBAT composite material according to claim 1 or 2, It is characterized in that The enzymatically degraded lignin is modified enzymatically degraded lignin; Optionally, the modified enzymatically hydrolyzed lignin includes at least one of sulfonated enzymatically hydrolyzed lignin, aminated enzymatically hydrolyzed lignin, alkylated enzymatically hydrolyzed lignin and etherified enzymatically hydrolyzed lignin; Optionally, the plasticizer includes at least one of deionized water, glycerol, ethylene glycol, polyethylene glycol, triacetin, dibutyl sebacate, acetyl tri-n-butyl citrate, triethyl citrate and tributyl citrate.

4. The enzymatically hydrolyzed lignin PBAT composite material according to claim 1 or 2, It is characterized in that The enzymatically hydrolyzed lignin PBAT composite material also includes: 0.2 to 1 parts by weight of a heat stabilizer, 0.5 to 1.5 parts by weight of a lubricant, and 0.1 to 1 parts by weight of an antioxidant, preferably 0.3 to 0.6 parts by weight of a heat stabilizer, 0.8 to 1.2 parts by weight of a lubricant, and 0.2 to 0.6 parts by weight of an antioxidant; optionally, the enzymatically hydrolyzed lignin PBAT composite material further includes 0.05 to 2 parts by weight of a chain extender.

5. The enzymatically hydrolyzed lignin PBAT composite material according to claim 4, It is characterized in that The heat stabilizer includes at least one of phosphoric acid, trimethyl phosphate, triphenyl phosphate, trimethyl phosphite and polyphosphoric acid; Optionally, the lubricant includes at least one of calcium stearate, zinc stearate, and oleamide lubricants; Optionally, the antioxidant includes at least one of antioxidant 618, antioxidant 1010, antioxidant 1076, and antioxidant 1178; Optionally, the chain extender includes at least one of hydroquinone dihydroxyethyl ether, resorcinol dihydroxyethyl ether, bisphenol A, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, and ethylene glycol.

6. A method for preparing the enzymatically hydrolyzed lignin PBAT composite material according to any one of claims 1 to 5, It is characterized in that include: (1) mixing dried enzymatically hydrolyzed lignin, PBAT and a plasticizer to obtain a premix; (2) The premix is ​​extruded and pelletized through a twin-screw extruder, and then cooled and pelletized to obtain an enzymatically hydrolyzed lignin PBAT composite material.

7. The method according to claim 6, It is characterized in that In step (1), the drying temperature is 25 to 40° C., and / or the drying time is 1 to 3 hours; Optionally, in step (1), the drying temperature is 29 to 31° C., and / or the drying time is 2 to 2.5 h, and the drying is preferably carried out under vacuum conditions with a vacuum degree of 5000 Pa or less, further 500 to 1000 Pa; Optionally, in step (1), the mixing temperature is 95 to 105° C., and / or the rotation speed is 800 to 1000 r / min, and / or the mixing time is 10 to 20 min; Optionally, in step (2), the extrusion temperature of the twin-screw extruder is 120 to 180° C., preferably 130 to 150° C.; Optionally, in step (1), the premix comprises 8 to 45 parts by weight of enzymatically hydrolyzed lignin, 55 to 92 parts by weight of PBAT, and 1 to 10 parts by weight of a plasticizer; Optionally, in step (1), the premix further comprises 0.2 to 1 parts by weight of a heat stabilizer, 0.5 to 1.5 parts by weight of a lubricant, and 0.1 to 1 parts by weight of an antioxidant; Optionally, in step (1), the premix further comprises 0.05 to 2 parts by weight of a chain extender; Optionally, the weight average molecular weight of the enzymatically hydrolyzed lignin is 4000 to 6000; Optionally, the particle size of the enzymatically hydrolyzed lignin is 1 to 10 μm; Optionally, the phenolic hydroxyl content of the enzymatically hydrolyzed lignin is 3 to 5 wt%; Optionally, the methoxy content of the enzymatically hydrolyzed lignin is 11 to 13 wt%.

8. The method according to claim 6 or 7, It is characterized in that In step (1), the enzymatically hydrolyzed lignin is subjected to a modification treatment in advance, wherein the modification treatment comprises at least one of sulfonation, amination, alkylation and etherification; Optionally, the plasticizer includes at least one of deionized water, glycerol, ethylene glycol, polyethylene glycol, triacetin, dibutyl sebacate, acetyl tri-n-butyl citrate, triethyl citrate and tributyl citrate; Optionally, the heat stabilizer includes at least one of phosphoric acid, trimethyl phosphate, triphenyl phosphate, trimethyl phosphite and polyphosphoric acid; Optionally, the lubricant includes at least one of calcium stearate, zinc stearate, and oleamide lubricants; Optionally, the antioxidant includes at least one of antioxidant 618, antioxidant 1010, antioxidant 1076, and antioxidant 1178; Optionally, the chain extender includes at least one of hydroquinone dihydroxyethyl ether, resorcinol dihydroxyethyl ether, bisphenol A, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, and ethylene glycol.

9. An enzymatically hydrolyzed lignin PBAT degradable film, It is characterized in that The enzymatically hydrolyzed lignin PBAT degradable film is prepared by using the enzymatically hydrolyzed lignin PBAT composite material according to any one of claims 1 to 5.

10. A method for preparing the enzymatically hydrolyzed lignin PBAT degradable film as claimed in claim 9, It is characterized in that The method comprises: putting the enzymatically hydrolyzed lignin PBAT composite material into a film blowing machine, and blowing the film to obtain the enzymatically hydrolyzed lignin PBAT degradable film; Optionally, the film blowing temperature of the film blowing machine is 120-190°C.

Citation Information

Patent Citations

  • Preparation method of full bio-based poly(butylene adipate-co-butylene terephthalate)ester with high molecular weight and excellent color and luster

    CN104031246A

Cited By

  • Full-biodegradable polyester resin and biological lignin composite thermal shrinkage film as well as preparation method and application thereof

    CN119842192A

  • Straw-based degradable rice transplanting covering film as well as preparation method and application thereof

    CN120945730A

  • Straw-based degradable plug seedling mulching film, preparation method and application thereof

    CN120945730B

  • Biodegradable material containing low-molecular-weight starch as well as preparation method and application of biodegradable material

    CN122502835A